Echoes - Tan, Isabel Hui Ling (2018)
“Echoes” is a 2D digitally-animated short film produced as a final year project. It tells the story of a lost dog trying to reconnect with its owner. The main themes of the film are loss and belonging. This report documents the process and development of making “Echoes”, from the pre-production to post-production. It elaborates on the challenges faced, and the solutions and compromises implemented in making this short film. Keywords: 2D Digital Animation, Hand-drawn Animation, Animated Short Film